(3GdGUWdGMGJ GdWHjIs
(3ChdgG (B:s
(3HSe Gddg GdQMef dQMje GdWH Yde HCMhGd HOf GdEfSGf ef LgI GdUMI hGdeQV hGdMGdI GdeJhSWI s
(3BNQgG (B:s
(3jJhY (B: (3gh cd fHGJ MGQ eSgd ebWY eMQb hGdHdZjI KdGKI ChRGfg EjQSG hKdKkG ScHjfL hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B39 - (3U(B73s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH (B- (3U (B24 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThGQi edi (B(1538) s
Keywords: (3GdWHs